2013
DOI: 10.1002/med.21297
|View full text |Cite
|
Sign up to set email alerts
|

Sigma‐2 Receptor Ligands and Their Perspectives in Cancer Diagnosis and Therapy

Abstract: The sigma-2 receptor is highly expressed in various rapidly proliferating cancer cells and regarded as a cancer cell biomarker. Selective sigma-2 ligands have been shown to specifically label the tumor sites, induce cancer cells to undergo apoptosis, and inhibit tumor growth. Sigma-2 ligands are potentially useful as cancer diagnostics, anticancer therapeutics, or adjuvant anticancer treatment agents. However, both the cloning of this receptor and the identification of its endogenous ligand have not been succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
98
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 145 publications
(210 reference statements)
0
98
0
Order By: Relevance
“…[29][30][31][32][33] Thus sigma-2 receptor may provide a new therapeutic target for the development of novel anti-cancer agents. 4,7,34 The mechanism of action of sigma-2 ligands is not yet entirely clear. But increasing evidence indicated that the apoptotic effects of sigma-2 ligands may involve multiple pathways that include the activation of caspases, inhibition of mTOR activities, disruption of ion channels, and induction of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[29][30][31][32][33] Thus sigma-2 receptor may provide a new therapeutic target for the development of novel anti-cancer agents. 4,7,34 The mechanism of action of sigma-2 ligands is not yet entirely clear. But increasing evidence indicated that the apoptotic effects of sigma-2 ligands may involve multiple pathways that include the activation of caspases, inhibition of mTOR activities, disruption of ion channels, and induction of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The sigma-2/PGRMC1 receptor is likely coupled to various cellular kinase pathways and thus the activation or inhibition of this receptor may regulate the cellular signal transduction and the fate of the cell. 4 Previously, we discovered that 6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline and 9-azabicyclo[3.3.1]nonane derivatives had high affinities for sigma-2 receptor and low or no affinities for sigma-1 receptor. [35][36][37] These two classes of analogs are still among the most selective sigma-2 ligands reported to date.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations